Facts of society and new spatialities - Monique Eleb; Sabri Bendimérad (VLC Arquitectura)
New spatial devices appear when society changes. Today families are restructuring, the domestic group is recomposing, practices are evolving and housing should follow. How can it be transformed to adapt to the life conditions and the lifestyle desired by singles of any age, families -either monoparental or blended-, by the elderly? Experiences in many countries are described here, showing the diversity of the devices proposed and their underlying ideals. They range from a simple practical solution to live in a contemporary way, particularly because of the porosity between habitat and work, to the ambition to change life starting with housing. Built in several countries, they also have very different scales. A simple house shared by friends in Japan or Holland, they can also gather very large groups in Sweden or Switzerland. A long survey on cohabitation in France helps to feed the authors’ reflection.